2020
DOI: 10.4187/respcare.07390
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Radiographic Bronchiectasis in COPD

Abstract: BACKGROUND: COPD and bronchiectasis frequently coexist, which creates an emerging phenotype with a worse prognosis. However, the impact of bronchiectasis on the natural history of COPD has not been fully evaluated and is still controversial. This meta-analysis was performed to clarify the associations of the presence of bronchiectasis with the prognosis and quality of life of patients with COPD. METHODS: A systematic review and meta-analysis was performed following a search of medical databases, and included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
(199 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, numerous studies have shown that this association has a more severe clinical presentation and worse prognosis than each individual disease [16,17,[33][34][35][36][37][38]. However, there is no consensus on how this association should be defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, numerous studies have shown that this association has a more severe clinical presentation and worse prognosis than each individual disease [16,17,[33][34][35][36][37][38]. However, there is no consensus on how this association should be defined.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of the association between COPD and BE is even less clear. In fact, the reported prevalence of BE in COPD patients varies considerably across series, from 4% to 75% [4,[15][16][17]. Different factors can be invoked to understand such variability in prevalence rates: series differ in inclusion criteria, severity of disease, definition of bronchiectasis and method used for radiological diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COPD bronchiectasis phenotype has special clinical characteristics, such as an excessive sputum volume, a higher risk of bacterial infection, including infection with P. aeruginosa , higher systemic and local inflammatory indexes, more frequent acute exacerbations, poor nutritional status, more severe airflow restriction, and immune imbalance. 17,18 These patients need to be treated for the two situations simultaneously as recommended in the corresponding guidelines. Some scholars have proposed that the area under the forced expiratory flow-volume loop is more suitable for the evaluation of emphysema in patients with bronchiectasis and COPD than the traditional parameters of spirometry and chest CT for guiding follow-up treatment.…”
Section: Etiologymentioning
confidence: 99%
“…Finally, airway obstruction is the oldest determinant of damages found in bronchiectasis. Laennec [26] identified for the first time this condition, which favors the onset of bronchiectasis in a wide group of conditions including: pulmonary structural alterationstypical of Williams-Campbell syndrome [27], Mounier-Kuhn syndrome [28] and Ehlers-Danlos syndrome [29]-single bronchial obstruction-as in case of neoplasms or foreign bodies-and, finally, obstructive diseases-such as asthma [30], chronic obstructive pulmonary disease (COPD) [31], and alpha-1-antitrypsin deficiency [32].…”
Section: Introductionmentioning
confidence: 99%